Penentuan Awal Bulan Kamariah Untuk Ibadah - Fathor Rahman; Pujiono Pujiono; Siti Muslifah (FENOMENA, 2020)
This paper presents data regarding the formula for determining the start of the month for worship at the time of the Prophet. This is important because the determination of the beginning of the month among Muslims has always been a polemic, even Muslims until now still do not have a definite and unique calendar to serve as a common guideline. The method usedin this research is the method introducedby Louay Safi "Unified Aproach to Shari'ah Inference"; namely textual normative inference, empirical-historical-contextualist inference, and integrated inference. The results were as follows: d natural inference stualis te k-normative-legis, fast orders clearly to be given information about ordinances that rukyatul hilal; and if it is cloudy or covered in fog, then it is ordered to calculate, estimate, or fulfill the month into 30 days and the rule of law in matters of mahdah worship such as fasting cannot be changed, sentences that are already text and sharih do not have the character of ijtihadi; and anything that creates controversy in society can be eliminated by the government or the authorities; whereas in the contextualist historical-empirical inference it can be said that worship which includes the obligation of rukyat has encouraged Muslims to study and deepen the science of astronomy ; and in unified inference, the computation of the reckoning at the time of the prophet with the fulfillment becomes thirty days because at that time the Madinans did not have zij or astronomical tables showing the positions of the moon, earth and sun. From this perspective, rukyat often called taabbudiy be part of the entity taaquliy for a silver lining can be found in the annals of the Muslims, and Reckoning ser ing said taaqquliy also part of ta'abbudiy entity because it is part and result of activity namely rukyat taabbudiy .